PENERAPAN SISTEM PENGENDALIAN INTERNAL UNTUK TRANSPARANSI DAN AKUNTABILITAS KEUANGAN KELURAHAN - Riduan Siagian; Jumadiah Wardati; Monang Tumangger (Jurnal Industri Kreatif dan Inovatif, 2024)
This article discusses the implementation of an Internal Control System (SPI) to improve transparency and financial accountability in village/urban-ward administration (kelurahan) in Indonesia. Without adequate controls, financial management may lead to risks such as incorrect record-keeping, unauthorized expenditures, incomplete transaction evidence, duplicate payments, delayed reporting, and low public transparency. The research aims to implement SPI by developing standard operating procedures (SOP) and key controls, mapping financial processes and risk points, providing simple administrative templates, training kelurahan staff, and establishing monitoring and reporting mechanisms (including a concise dashboard). The SPI framework follows common practices (e.g., COSO) adapted to the kelurahan context, covering control environment, risk assessment, control activities (authorization, segregation of duties, document controls, reconciliation, and access restrictions), information and communication, and monitoring. The expected outputs include SPI policy documents, administrative templates (transaction registers, evidence checklists, minutes/record forms, reconciliation formats, and asset logs), as well as a dashboard for realization and document compliance. The findings indicate that implementing SPI can significantly improve financial compliance and accountability, though several challenges still need to be addressed to ensure the system’s sustainability.